Prilagoditvene spretnosti - Stropnik, Staša (Psihološka obzorja (Ljubljana), 2012)
Adaptive skills are defined as a collection of conceptual, social and practical skills that are learned by people in order to function in their everyday lives. They include an individual's ability to adapt to and manage her or his surroundings to effectively function and meet social or community expectations. Good adaptive skills promote individual's independence in different environments, whereas poorly developed adaptive skills are connected to individual's dependency and with greater need for control and help with everyday tasks. Assessment of adaptive skills is often connected to assessment of intellectual disability, due to the reason that the diagnosis of intellectual disability includes lower levels of achievements on standardized tests of intellectual abilities as well as important deficits in adaptive skills. Assessment of adaptive behavior is a part of standard assessment battery with children and adults with different problems, disorders or disabilities that affect their everyday functioning. This contribution also presents psychometric tools most regularly used for assessment of adaptive skills and characteristics of adaptive skills with individual clinical groups.
Keywords: prilagoditvene spretnosti; duševni razvoj; motnje